Effect of Empagliflozin Beyond Glycemic Control: Cardiovascular Benefit in Patients with Type 2 Diabetes and Established Cardiovascular Disease - Monteiro, P (2021)
Submitted by Ana Quininha (ana.quininha@chlc.min-saude.pt) on 2021-02-05T16:45:08Z No. of bitstreams: 1 RPC 2019 721.pdf: 1327108 bytes, checksum: e750a5ed0fc728132c3345f4ec35e04d (MD5)